Keterkaitan antara Kadar Silikon dan Aluminium dari Kandungan Debu Tanah Hasil Perlakuan Basa atau Asam dalam Kemampuannya Mengadsorpsi Biru Metilen - Suhendar, Dede; Agustini, Fresa (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Soil dust is the most difficult object of research to find in applications, even though it is rich in silica, silicate, and aluminosilicate compounds, which are widely known as adsorbents. The physical and chemical characteristics of compounds in which the main framework is the oxides of silicon and aluminum in the material are usually related to their Si/Al mole ratio. This study aims to study the effect of changes in the levels of silicon, aluminum, and related elements in alkaline or acid-treated soil dust (DTBA) in adsorbing methylene blue (MB). The difference in the composition of the elements in DTBA is expressed in terms of the mole ratios of silicon to aluminum, (Si/Al)mole, the ratio of moles of silicon to the number of moles of aluminum and iron, (Si/(Al+Fe))mole, the ratio of moles of silicon to the number of moles of aluminum, iron, and calcium, (Si/(Al+Fe+Ca))mole, and the mole difference of silicon to aluminum, (Si-Al)mole. The quantities in moles were also tested using the levels of these elements: (Si/Al)weight, (Si/(Al+Fe))weight, (Si/(Al+Fe+Ca)weight, and (Si–Al)weight. Through linear and non-linear regression (2nd order polynomial), plotting of the concentration of adsorbed MB to (Si–Al)weight had the highest correlation coefficient (R2 = 0.9767), better than (Si/Al)mole (polynomial 2, R2 = 0.5177), (Si/(Al+Fe))mole (polynomial 2, R2 = 0.7940), and (Si/(Al+Fe+Ca))mole (linear, R2 = 0.7996) or the same based on percentage of weight, (Si/Al)weight (polynomial 2, R2 = 0.9105), (Si/(Al+Fe))weight (polynomial 2, R2 = 0.6649), and (Si/(Al+Fe+Ca))weight = (polynomial 2, R2 = 0.5601). From a number of optimizations, the adsorption of MB on DTBA was close to the Langmuir and Redlich-Peterson isotherm adsorption model, which describes that there was one layer of MB adsorbate on the surface of DTBA. With this result, soil dust resulting from alkaline or acid treatment can adsorb MB on its surface, which is determined most by the difference in the weight of silicon to aluminum.